Korelasi Antara Motivasi Berpestasi dan Kepercayaan diri Terhadap Prestasi Atlet Renang Mutiara Swimming Club - Prayoga Restu Samudra; Sungkowo Sungkowo (Jurnal Porkes, 2026)
This study aimed to determine the correlation between achievement motivation and self-confidence toward athlete achievement at Mutiara Swimming Club. This research employed a quantitative correlational design. The population consisted of 60 athletes, while the sample involved 26 athletes selected through purposive sampling with the criteria of being 10–19 years old and having participated in and won swimming competitions within the last year. Data were collected using achievement motivation and self-confidence questionnaires as well as athlete achievement records. Data analysis IBM SPSS Statistics version 27. The results showed that most athletes had high levels of achievement motivation and self-confidence. Pearson correlation analysis indicated a positive and significant relationship between achievement motivation and self-confidence (r = 0.623; p < 0.01). However, achievement motivation did not show a significant relationship with athlete achievement (r = 0.305; p > 0.05), while self-confidence also showed a very weak and insignificant relationship with athlete achievement (r = 0.100; p > 0.05). Multiple regression analysis showed that achievement motivation and self-confidence simultaneously did not significantly influence athlete achievement (F = 1.371; p > 0.05). Therefore, athlete achievement is likely influenced by other factors such as physical condition, technical skills, training quality, and competition experience.